The pregnant woman with heart disease: management of pregnancy and delivery - Pieper, P. G. (Bohn Stafleu van Loghum, 2011)
Women with heart disease are at risk of cardiac complications during pregnancy and delivery. Risk assessment should be performed in these women, and the management of pregnancy and delivery should be planned accordingly. Depending on the risk, women should be cared for in specialised centres, regional centres or a combination of both. Multidisciplinary teams must be involved in the care of these women. Adequate organisation of care and communication between the team members is important to prevent complications.